2004
DOI: 10.1016/s0002-9440(10)63180-x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening Occurs in Subsets of Normal Breast Epithelium as well as in Situ and Invasive Carcinoma

Abstract: In the setting of inactivated DNA damage-sensitive checkpoints, critically shortened telomeres promote chromosomal instability and the types of widespread cytogenetic alterations that characterize most human carcinomas. Using a direct telomere fluorescence in situ hybridization technique, we analyzed 114 invasive breast carcinomas, 29 carcinoma in situ lesions, 10 benign proliferative lesions, and different normal epithelial components of the male and female breast. We found marked telomere shortening in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
121
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 39 publications
12
121
2
1
Order By: Relevance
“…Recently, abnormalities have been appreciated in histologically normal breast epithelium. These abnormalities include allelic imbalance or loss of heterozygosity, [1][2][3][4][5][6][7][8] aberrant methylation of p16 INK4 9 and of RASSF1A, 10 cytogenetic changes, 11,12 telomere shortening, 13 loss of IGF2 imprinting, 14 aberrant response to estrogen, 15 loss of RARb expression, 16 aberrant phosporylation of p38, 17 upregulation of EZH2. 18 Some of these abnormalities have been detected in normal-appearing tissue adjacent to the tumor, and others have been found at a distance from it.…”
mentioning
confidence: 99%
“…Recently, abnormalities have been appreciated in histologically normal breast epithelium. These abnormalities include allelic imbalance or loss of heterozygosity, [1][2][3][4][5][6][7][8] aberrant methylation of p16 INK4 9 and of RASSF1A, 10 cytogenetic changes, 11,12 telomere shortening, 13 loss of IGF2 imprinting, 14 aberrant response to estrogen, 15 loss of RARb expression, 16 aberrant phosporylation of p38, 17 upregulation of EZH2. 18 Some of these abnormalities have been detected in normal-appearing tissue adjacent to the tumor, and others have been found at a distance from it.…”
mentioning
confidence: 99%
“…This finding parallels our previous studies in tumors of the prostate and their matched TA-HN tissues, 28 and is in agreement with the work of previous investigators who reported that genetic alterations, including telomere attrition and loss of heterozygosity, occur in histologically normal tissues adjacent to breast tumors. [34][35][36][37][38][41][42][43][44] In these previous studies, the sites of telomere attrition, loss of heterozygosity, and AI were physically distant from one another and from the tumors, albeit in most cases at undefined distances from the corresponding tumor lesions. 24,[42][43][44] In contrast, and to our knowledge, the findings in cohort 1 represent the first study in breast cancers that analyzes genomic instability at defined distances (1 cm and 5 cm) from the visible tumor margins.…”
Section: Discussionmentioning
confidence: 89%
“…[34][35][36][37][38][41][42][43][44] In these previous studies, the sites of telomere attrition, loss of heterozygosity, and AI were physically distant from one another and from the tumors, albeit in most cases at undefined distances from the corresponding tumor lesions. 24,[42][43][44] In contrast, and to our knowledge, the findings in cohort 1 represent the first study in breast cancers that analyzes genomic instability at defined distances (1 cm and 5 cm) from the visible tumor margins. Consequently, this study reveals that genomic instability in tumor adjacent, histologically normal breast tissues is a function of distance from the tumor lesion, showing decreasing extent of genomic instability with increasing distance from the tumor margin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results suggest early focal appearance of thyrocytes with abnormal telomere phenotypes which may contribute to FTC in the Thrb PV/PV mouse model. Precancerous stages and cancer can both present with telomere shortening (38,39), and FISH-based detection of shorter telomeres in histological specimens was shown to be an early event in human prostate, pancreas, bladder, large intestine, esophagus, oral cavity, and uterine cervix cancer development (39)(40)(41). However, shorter telomeres are not always associated with cancer but have also been described in breast ductal carcinoma in situ and in normal breast secretory cells (38).…”
Section: Discussionmentioning
confidence: 99%